2008
DOI: 10.1111/j.1365-2672.2007.03599.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of fermentation condition for antibiotic production by Xenorhabdus nematophila with response surface methodology

Abstract: Aims:  To evaluate the influence of environmental parameters on the production of antibiotics (xenocoumacins and nematophin) by Xenorhabdus nematophila and enhance the antibiotic activity. Methods and Results:  Response surface methodology (RSM) was employed to study the effects of five parameters (the initial pH, medium volume in flask, rotary speed, temperature and inoculation volume) on the production of antibiotics in flask cultures by X. nematophila YL001. A 25−1‐factorial central composite design was cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 28 publications
6
32
0
Order By: Relevance
“…The adjusted determination is 0.9655, which shows the regression model is significant with an adequate precision is more than 4, which is 38.862. The model is more significant if R2 value is closer to 1 [15]. The standard deviation for this model is 4.683×10-3 and this value indicate that it is relatively lower than 0.05 which is good for better precision and reliability of the experiment [16].…”
Section: Response Surface Methodology (Rsm) Regression Analysismentioning
confidence: 77%
“…The adjusted determination is 0.9655, which shows the regression model is significant with an adequate precision is more than 4, which is 38.862. The model is more significant if R2 value is closer to 1 [15]. The standard deviation for this model is 4.683×10-3 and this value indicate that it is relatively lower than 0.05 which is good for better precision and reliability of the experiment [16].…”
Section: Response Surface Methodology (Rsm) Regression Analysismentioning
confidence: 77%
“…The adjusted determination is 0.9618, which indicated that the regression model is significant with an adequate precision is more than 4, which is 37.564. The model is more significant if R 2 value is closer to 1 [14]. The standard deviation for this model is 8.807×10-3 and this value indicated that it is relatively lower than 0.05 which is better for precision and reliability of the experiment [15].…”
Section: Response Surface Methodology (Rsm) Regression Analysismentioning
confidence: 80%
“…The adjusted determination is 0.9655, which shows the regression model is significant with an adequate precision is more than 4, which is 38.862. The model is more significant if R2 value is closer to 1 [16]. The standard deviation for this model is 4.683×10-3 and this value indicate that it is relatively lower than 0.05 which is good for better precision and reliability of the experiment [17].…”
Section: Response Surface Methodology (Rsm) Regression Analysismentioning
confidence: 84%